Non-invasive prenatal test for first-tier trisomy screening in general pregnant population: a pilot study - Heino, Sara (My University, 2026)
First trimester aneuploidy screening is regulated by a national statute in Finland. According to the national screening statue from 2009, the first trimester combined test (FCT), including early pregnancy placental biomarker analyses and an ultrasound scan, was used for early pregnancy chromosomal screening. After the re-evaluation of screening protocols in 2023, the test method was removed from the statute. Globally, non-invasive prenatal testing (NIPT) is widely used as a second-tier test after a high risk FCT result, but its use as a first-tier screening in general population is still limited and mainly used in high risk populations. The aims of this study were explore the implementation of NIPT as a first-tier trisomy screening test in the entire pregnant population of the welfare area of Southwest Finland, and compare the screening results to an earlier historic cohort screened with FCT. This prospective real-life NIPT-implementation study in general population of Southwest Finland included pregnant women screened with NIPT in in 2023-2024, and the results were compared to a historic cohort screened with FCT in 2019- 2022. The primary outcomes in this study were the participation rates and test performances for trisomies 21, 18 and 13. In Southwest Finland, nearly all women in the general pregnant population participated in cost-free chromosomal screening during both, FCT and NIPT screening periods. First-tier NIPT had very high sensitivity and specificity in the detection of trisomies 21, 18 and 13, and its positive predictive value was significantly higher than with FCT. In conclusion, after the transition from the FCT to first-tier NIPT, the participation rate in prenatal aneuploidy screening remained high. Consistent with earlier studies, NIPT demonstrated better performance than FCT, which lead to reduction in the need of supplementary testing.
Keywords: chromosomes, early pregnancy, fetal screening, first-trimester combined test, non-invasive prenatal test, trisomy 13, trisomy 18, trisomy 21